IVIG response in pediatric acute-onset neuropsychiatric syndrome correlates with reduction in pro-inflammatory monocytes and neuropsychiatric measures - Melamed, Isaac; Rahman, Shamma; Pein, Heather; Heffron, Melinda; Frankovich, Jennifer; Kreuwel, Huub; Mellins, Elizabeth D. (Frontiers in Immunology, 2024)
reports on new data exploring the link between inflammation in Pediatric Acute-Onset Neuropsychiatric Syndrome (PANS) and its improvement with IVIG treatment. Previous research has shown that IVIG infusions can correlate with reduced psychiatric symptoms. In this study we additionally evaluated pro-inflammatory myeloid cells (monocytes and dendritic cells), as well as clinical assessments including Tic and OCD scales over 18 weeks of treatment and at 1 and 8 weeks of post-treatment follow-up. The results strongly suggest an association of PANS with a proinflammatory state, which improves following treatment with IVIG.We believe these results are of clinical interest to the journal's readership, and of vital importance for the ongoing treatment and management of PANS. We are showing, for the first time, that IVIG treatment both reduces pro-inflammatory myeloid cell frequency and improves psychiatric symptoms scores. IVIG may therefore be a part of the clinical treatment path for patients with PANS, particularly those with severe and moderate disease, as included in this study.